2021
DOI: 10.37391/ijeer.090304
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Particle Swarm Optimization for Prediction of Accident Severity

Abstract: In recent time, road traffic accidents are increased day by day due to incremental growth in number of vehicles. Traffic accidents are also the crucial and important issue for achieving the sustainable transportation development. One of the tasks of sustainable transportation is to reduce the number of accidents and also design the traffic assessment policy. Many researchers consider the traffic accident issue of sustainable transportation and developed prediction models for measuring severity of accidents. Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The study demonstrated that IPSO achieves superior results in terms of accuracy, precision, and recall when compared to other techniques. It also highlighted the potential for using other meta-heuristic algorithms and feature selection techniques in future research to further enhance accident severity prediction [5].…”
Section: Feature Selectionmentioning
confidence: 99%
“…The study demonstrated that IPSO achieves superior results in terms of accuracy, precision, and recall when compared to other techniques. It also highlighted the potential for using other meta-heuristic algorithms and feature selection techniques in future research to further enhance accident severity prediction [5].…”
Section: Feature Selectionmentioning
confidence: 99%
“…A method for automatic categorization of standard macular appearances in spectral-domain OCT (SD-OCT) volumes was published in 2010 along with a common confined retinal irregularity approach [20]. The intraregional segmentation detection technique was compared with the orientation ordinary established by two experts [10,21].…”
Section: ░ 2 Related Workmentioning
confidence: 99%
“…For uplink MIMO system, still the linear detectors perform matrix inversion for detecting the signal. It gives high computational complexity and degrades the performance [2].…”
Section: ░1 Introductionmentioning
confidence: 99%